Earth beyond repair: Race and apocalypse in collective imagination. (February 2020) - Gergan, Mabel; Smith, Sara; Vasudevan, Pavithra
Scholars have argued that geologic proposals for the Anthropocene are entangled with collective imaginaries and geopolitical anxieties. In this article, we analyze three prominent tropes of American apocalyptic films (the "Great Deluge, " the "Nuclear Catacalysm, " and "the Population Bomb") and map them onto existing geological proposals for the Anthropocene. In staging this encounter, we illustrate how impending ecological disasters in American popular imagination temporally displace the apocalypse into the present or the future. These imaginings of apocalypse evade specific culpability when they imagine a universal human frailty, enacting a darkly ironic reversal of historical and ongoing apocalyptic realities. Drawing on insights from ecocriticism, political geography, postcolonial, decolonial and critical race studies, we argue that the global crisis heralded by the Anthropocene reveals deep-seated fears of racialized others taking over the planet and the decline of white civilization, and we suggest alternative openings for other futures.